The evolution of energy policy in Western Europe : the reluctant retreat from coal - Gordon, Richard L. (New York : Praeger, 1970)
This study begins with a brief survey of Europe's role in the world energy market (Chapter 1). In Chapter 2, the history of European energy policy is related. Chapters 3 and 4 discuss the basic data on energy market conditions; the first deals with demand conditions and external supply developments and how Europeans appraised them, while the second, with domestic energy market conditions. Chapter 5 deals with efforts to formulate a coordinated energy policy. Theoretical models appear in Chapter 6, and the last chapter provides an evaluation of intervention.
Includes bibliographical references: p. 325-330.
ne 17/04/2018
Loans
Keywords: Energy Policy